(untitled) (Scientific journal of the Fergana State University, 2025)
In this research work, m-cresol was reacted with chloroacetyl chloride under different conditions. When m-cresol is reacted with chloroacetyl chloride in the presence of catalytic amounts of FeCl3, FeCl3×6H2O, ZnCl2, Fe2(SO4)3 and TAA, it was found that a mixture of isomers is formed. When research was continued with the aim of synthesizing an individual substance, a method of synthesizing m-tolylchloroacetate in a benzene solution was found. The reaction mechanism of this reaction was developed and theoretically justified. Nucleophilic exchange reaction of m-Tolylchloroacetate with 4-methylphenol was carried out in benzene, acetone, dioxane, DMF, DMSO solutions. The yield of the reaction was high in DMSO solution, and the yield of m-tolyl-4-methylphenoxyacetate was 95%.